The Challenges and Therapeutic Prospects in Eye Disease - Tsai, Chieh-Chih (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aims to update the current evidence and challenging topics centred around the diagnosis and management of ocular diseases. We gather ten original research articles and two literature reviews on recent efforts aimed toward the discovery of novel findings in different ocular research areas, including orbital, lacrimal, and eyelid disease, as well as glaucoma, retinal disease, myopia, and corneal disease.